Implications of Local Potential-Based STEM Learning Model on Student Creativity - Sulaeman, Wiska Hera Sagita; Windyariani, Sistiana; Nurlathifah, Zulfa; Setiono, Setiono (BIOEDUKASI, 2024)
This research is motivated by the low creativity of students in learning biology at school. The purpose of this study was to determine how the implications of ethnoscience-based STEM learning models on student creativity on excretory system material. This study used a quantitative approach, quasi-experimental method with non-equivalient control group design, in the selection of samples by purposive sampling. The instruments used were verbal and figural creativity tests, product creativity assessment and student response questionnaires to ethnoscience-based STEM learning models. The research subjects were junior high school students in grade VIII with 27 experimental class students and 27 control class students. The results showed that the ethnoscience-based STEM learning model implies student creativity, this is known from the results of hypothesis testing showing H₀ is rejected and Hₗ is accepted with the results of Sig (2-tailed) verbal creativity 0.000 and figural creativity 0.001 so that the data can be said to be significantly different. The implications of the learning model can also be seen from the N-Gain value of verbal creativity of the experimental class which is 0.65 and the control class is 0.48 while the N-Gain value of figural creativity of the experimental class is 0.63 and the control class is 0.45. The average student response questionnaire is 81.79% or in the very good category. The conclusion of this research is that there is an implication of ethnoscience-based STEM learning model on the creativity of students of one of the Sukabumi District State Junior High School.